PELAYANAN PEMBUATAN KARTU KELUARGA (KK) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BENGKAYANG - irmawati, irmawati; Zulkarnaen, Zulkarnaen; Triyono, Joko (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2024)
This study aimed to describe and analyze the service quality of making the Family Register in the Bengkayang Regency Civil Registry Service Department. This research used a descriptive study with a qualitative approach. This study used Zeithmal, Pasuraman, and Berry’s Service Quality theory (in Ratminto, 2019: 175) which consisted of reliability, responsiveness, assurance, empathy, and physical evidence. The results showed that the officers’ reliability in providing services was still lacking, the officers had been quite responsive in responding to the service recipient community, the officers could not provide certainty on the completion time of making a Family Register, the employees had given quite good empathy, and there were still many shortcomings, especially in terms of office buildings. The researcher suggests that the employees must have the ability and expertise in making the civil register documents, all officers must be able to provide a responsive attitude to the service user community, they also must handle complaints or suggestions from the community properly and it is hoped that officers can complete the making of Family Register according to the set time. Keywords: Service; Quality; Making The Family Register